Hereditary thrombotic thrombocytopenic purpura mimicking immune thrombocytopenia was revealed by miscarriage-novel compound heterozygous mutations in hTTP - Ruiqing Zhou; Jiahuan Wang; Ahui Wang; Shunqing Wang; Yumiao Li; Shilin Xu; Wenjian Mo (BMC, 2024)
Abstract We report a case of early-onset hereditary thrombotic thrombocytopenic purpura in a 16-year-old girl who suffered from thrombocytopenia and was misdiagnosed with immune thrombocytopenia for years until two failed gestations finally revealed the underlying cause. The novel compound heterozygous mutation c.2865G > A:p.Trp955X and c.721delG: p.Gly241fs in the ADAMTS13 gene were identified and are predicted to be associated with this disease. The patient responded to plasma therapy, including plasma infusion and plasma exchange, but renal dysfunction may be longstanding.